Cost-effectiveness of pneumococcal vaccination for elderly in Sweden. Issue 32 (6th July 2020) - Wolff, Ellen; Storsaeter, Jann; Örtqvist, Åke; Naucler, Pontus; Larsson, Sofie; Lepp, Tiia; Roth, Adam
Highlights: Cost-effectiveness analysis of pneumococcal vaccination to 65- and 75-year-olds. Compartmental model investigating cost- and health-effects of pneumococcal burden of disease. Pneumococcal vaccination of 65-year-olds cannot be considered good value for money in Sweden. Pneumococcal vaccination of 75-year-olds would be good value for money in Sweden. Abstract: Introduction: The aim was to assess cost-effectiveness of including pneumococcal vaccination for elderly in a national vaccination programme in Sweden, comparing health-effects and costs of pneumococcal related diseases with a vaccination programme versus no vaccination. Method: We used a single-cohort deterministic decision-tree model to simulate the current burden of pneumococcal disease in Sweden. The model accounted for invasive pneumococcal disease (IPD) and pneumonia caused by pneumococci. Costs included in the analysis were those incurred when treating pneumococcal disease, and acquisition and administration of the vaccine. Health effects were measured as quality-adjusted life years (QALY). The time-horizon was set to five years, both effects and costs were discounted by 3% annually. Health-effects and costs were accumulated over the time-horizon and used to create an incremental cost-effectiveness ratio. The 23-valent polysaccharide vaccine (PPV23) was used in the base-case analysis. The 13-valent pneumococcal conjugate vaccine PCV13 was included in sensitivity analyses. Results: A vaccination programme using PPV23 would reduce the burden of pneumococcal related disease significantly, both when vaccinating a 65-year-old cohort and a 75-year-old cohort. IPD would decrease by 30% in the 65-year-old cohort, and by 29% in the 75-year-old cohort. The corresponding figures for CAP (communicable acquired pneumonia) are 19% and 15%. The cost per gained QALY was estimated to EUR 94, 000 for vaccinating 65-year-olds and EUR 29, 500 for 75-year-olds. With one dose PCV13 given instead of PPV23, the cost per gained QALY would increase by around 400% for both cohorts. The results were robust in sensitivity analyses. Conclusion: Introducing a vaccination programme against pneumococcal disease for 65-year-olds in Sweden is unlikely to be cost-effective, whereas it for 75 year-olds and using PPV23 can be considered good value for money. Our model indicates that vaccine price needs to be reduced by 55% for vaccination of 65-year-olds to be cost-effective, given a threshold of EUR 50, 000.